2015
DOI: 10.3402/gha.v8.26227
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, awareness, and control of hypertension among workers in West Africa: a systematic review

Abstract: BackgroundInterventions in workplace settings are considered to be cost-effective in preventing cardiovascular diseases. A systematic review was conducted to assess the prevalence of hypertension and the level of awareness and control among workers in West Africa.DesignA systematic search for studies on formal and informal sector workers aged ≥15 years in West Africa published between 1980 and September 2014 was undertaken using the Ovid Medline, Embase, PubMed, and Google Scholar databases. Clinical and obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 84 publications
3
52
5
4
Order By: Relevance
“…We found different data from 19.6% to 84% [19] and 16.9%, 29.2% and 33.7% respectively for 1990, 2000 and 2010 [5].…”
Section: Discussioncontrasting
confidence: 61%
“…We found different data from 19.6% to 84% [19] and 16.9%, 29.2% and 33.7% respectively for 1990, 2000 and 2010 [5].…”
Section: Discussioncontrasting
confidence: 61%
“…Bosu [24] noted a high prevalence of hypertension among West Africa's workforce, of which a significant proportion is undiagnosed, severe, or complicated. The crude prevalence of hypertension increased progressively from 12.9 % in studies published in the 1980s to 34.4 % in those published in 2010-2014.…”
Section: Epidemiology Of Hypertension In Low-income Countriesmentioning
confidence: 99%
“…Reproduced with permission from Ref. 24 A favorite recommendation to control hypertension is to reduce body mass index (BMI), as it is a well-documented fact that increased BMI is one of the reasons behind the increasing prevalence of hypertension. However, attempts at lowering BMI through population-wide interventions have so far failed [34].…”
Section: How To Improve Hypertension Controlmentioning
confidence: 99%
“…A study in Abuja reported a high prevalence of hypertension among the elderly populations, and majority of whom were unaware about their conditions [102]. Other studies have suggested that low levels of knowledge and awareness of hypertension are associated with undiagnosed, severe or complicated, and uncontrolled hypertension [103], lack of patients' adherence to lifestyle modifications and to medications [104,105]. Certainly raising awareness particularly on uptake of screening services for most NCDs could be beneficial at both individual and population-levels.…”
Section: Lack Of Community Awarenessmentioning
confidence: 99%